2010
DOI: 10.1063/1.3302468
|View full text |Cite
|
Sign up to set email alerts
|

Surface-induced magnetism in C-doped SnO2

Abstract: The magnetism of C-doped SnO2 (001) surfaces is studied using first-principles calculations. It is found that carbon does not induce magnetism in bulk SnO2 when located at the oxygen site, but shows a large magnetic moment at the SnO2 (001) surface. The magnetic moment is mainly contributed by the carbon atoms due to empty minority spins of p orbitals and is localized at the surface and subsurface atoms. No magnetism is observed when the carbon atom is located at the subsurface oxygen sites. The origin of magn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 27 publications
3
42
2
Order By: Relevance
“…Neutral and doubly ionized oxygen vacancies on (001) and (110) surfaces are also found to be non-magnetic as in the case of bulk; this is in agreement with previous DFT-GGA results. 23 However, singly ionized oxygen vacancies are found to be magnetic on (001) surface and nonmagnetic (110) surface.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…Neutral and doubly ionized oxygen vacancies on (001) and (110) surfaces are also found to be non-magnetic as in the case of bulk; this is in agreement with previous DFT-GGA results. 23 However, singly ionized oxygen vacancies are found to be magnetic on (001) surface and nonmagnetic (110) surface.…”
Section: -mentioning
confidence: 99%
“…It has also been found that even nonmagnetic-nonmetallic atoms like C, N, and nonmagnetic, alkali metallic atoms like Mg, K can also induce magnetism in oxides. 23,47 Nanoparticles having radius of only a few nanometers will have a large surface-to-volume ratio. The effect of surfaces in inducing the magnetism in oxide nanoparticles while doped with either magnetic or nonmagnetic atoms has not been investigated in detail.…”
Section: -mentioning
confidence: 99%
“…[1][2][3] SnO 2 has been extensively researched as a dilute magnetic semiconductor since Dietl 4 predicted room temperature ferromagnetism (RTFM) in Mn-doped ZnO 4 , and several theoretical models propose to explain observations of RTFM in SnO 2 . [5][6][7] Recent computational work predicts RTFM in SnO 2 due to nitrogen substitution 8 , surface carbon 9 , or non-magnetic dopants. 10,11 Raman et al proposed RTFM due to tin vacancies 12 , but V sn is not considered thermodynamically favorable.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] To go beyond vacancy-induced magnetism, we also proposed possible magnetism induced by light elements, e.g., C, and Li. 24,25 Recent theoretical calculations further show that magnetism can be induced with NM impurities. [2][3][4]26,27 A good example of NM impurity is carbon, which has been shown theoretically and experimentally that C-doped SnO 2 films can exhibit feromagnetic behaviour at room temperature, 24,28 where C does not induce magnetism in bulk SnO 2 , when located at the oxygen site.…”
mentioning
confidence: 99%
“…24,25 Recent theoretical calculations further show that magnetism can be induced with NM impurities. [2][3][4]26,27 A good example of NM impurity is carbon, which has been shown theoretically and experimentally that C-doped SnO 2 films can exhibit feromagnetic behaviour at room temperature, 24,28 where C does not induce magnetism in bulk SnO 2 , when located at the oxygen site. 24,28 Now, it is a firm belief that magnetism in NM hosts can be tuned either by vacancies or light elements.…”
mentioning
confidence: 99%